Mental training tools to build up interference tolerance in volleyball players - Bulykina, L. V.; Romanina, E, V.; Khoreva, J. A.; Grigoriev, V. A. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2017)
The study was designed to profile the mental effects of distracting factors on the competitive performance in volleyball and develop the mental conditioning recommendations to build up the interference tolerance in players. Subject to the questioning survey were 100 women volleyball players from the Premier League of the Russian Volleyball Championship and the Students` Volleyball League of Russia. The subjects were dominated by the Candidates for Master of Sport and Class I Athletes. The study obtained experimental data to detect and analyze a variety of objective and subjective distracting factors in volleyball of negatively effects on the players` attention and game actions. The data and analyses provided a basis for the mental conditioning recommendations to build up the interference tolerance in players i.e. minimize the negative effects of the distracting factors on the mental and technical responses of players and thereby improve the tactical and technical aspects of their performance and, hence, the overall competitive success.